2017
DOI: 10.2340/16501977-2249
|View full text |Cite
|
Sign up to set email alerts
|

Are job strain and sleep disturbances prognostic factors for low-back pain? A cohort study of a general population of working age in Sweden

Abstract: The aim of this study was to determine whether job strain, i.e. a combination of job demands and decision latitude (job control), and sleep disturbances among persons with occasional low-back pain are prognostic factors for developing troublesome low-back pain; and to determine whether sleep disturbances modify the potential association between job strain and troublesome low-back pain. A population-based cohort from the Stockholm Public Health Cohort surveys in 2006 and 2010 (= 25,167) included individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…A recent study of patients with LBP showed that co-existing sleep problems lowered the probability of recovering from LBP at 6 months follow-up 7. Furthermore, an observational study of persons with occasional LBP showed that sleep problems increased the risk of developing troublesome LBP at 4 years follow-up 10. The current study expands on these findings by showing that frequency of sleeplessness and number of insomnia symptoms are inversely and dose-dependently associated with the long-term prognosis of chronic LBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of patients with LBP showed that co-existing sleep problems lowered the probability of recovering from LBP at 6 months follow-up 7. Furthermore, an observational study of persons with occasional LBP showed that sleep problems increased the risk of developing troublesome LBP at 4 years follow-up 10. The current study expands on these findings by showing that frequency of sleeplessness and number of insomnia symptoms are inversely and dose-dependently associated with the long-term prognosis of chronic LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experimental studies have revealed a possible pathway between poor sleep and pain by showing that sleep deprivation leads to elevated levels of pro-inflammatory cytokines8 and alterations in central pain processing 9. One observational study has shown that occasional LBP and co-existing sleep problems are associated with higher risk of troublesome LBP 10. However, there is a lack of studies investigating the influence of sleep problems on long-term prognosis of chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…According to other studies , pain intensity positively correlates with sleep disorders as confirmed by own study. However, the studies conducted among the working population showed that insomnia seems to be a risk factor for the development of back pain.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing recognition that LBP is a biopsychosocial disorder, which can be influenced by a range of interacting factors 2 13. These can include pathoanatomical (eg, disc degeneration),14 15 physical (eg, protective muscle guarding, deconditioning),16–18 psychological (eg, back pain beliefs, depression, fear of activity, pain self-efficacy),19–22 lifestyle (eg, physical inactivity, sleep deficits, stress)23–25 and social (eg, culture, socioeconomic status, work and family life)26 27 factors, which vary from individual to individual. While many claim we need to target these factors (where modifiable),13 28–30 there is debate as to whether more individualised interventions can provide better clinical outcomes than standardised interventions for LBP.…”
Section: Introductionmentioning
confidence: 99%